Synergistic Effect of Temperature and Electrolyte Concentration on Solid‐State Interphase for High‐Performance Lithium Metal Batteries - Li, Quan; Xue, Weiran; Peng, Jiayue; Yang, Lufeng; Pan, Hongyi; Yu, Xiqian; Li, Hong (Advanced energy and sustainability research, 2021)
Lithium metal batteries (LMBs) are considered as the development direction of next‐generation rechargeable lithium batteries owing to their high energy densities. The electrochemical and safety performances of LMBs are significantly influenced by the solid electrolyte interphase (SEI) formed on the surface of lithium anode. Herein, the effects of both salt concentration and temperature on the SEI composition and properties are systematically investigated. The results reveal that either reducing the salt concentration to ultralow levels or elevating the temperature can lead to a more complete decomposition of the LiFSI salt. Meanwhile, the LiNO3‐rich SEI formed in the most dilute electrolyte (0.1 m) exhibits a better protective effect on lithium metal than the Li3N‐rich SEI formed in other electrolytes with higher salt concentrations. Benefiting from the compact and stable SEI, Li|Li4Ti5O12 batteries using the 0.1 m electrolyte possess the most superior cycling and rate performance at high temperature. This work generates a holistic understanding of the synergistic effects of salt concentration and temperature on SEI. Moreover, the utilization of dilute electrolytes not only renders a superior electrochemical performance of batteries at high temperature, but can also lower the production cost of electrolytes, showing a promising application potential in LMBs. Synergistic effects of salt concentration and temperature on solid electrolyte interphase (SEI) and battery performance are systematically investigated. Either reducing the salt concentration or elevating the temperature can result in a more complete salt degradation. LiNO3‐rich SEI shows a better protective effect on lithium metal than the Li3N‐rich SEI, which renders Li metal batteries superior in cyclic and rate performance.